PENGARUH PROFITABILITAS DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2006 – 2010 - Sri Lestari (STIKOM CKI, 2016)
The purpose of this research is to empirically study effect of net profitability and dividend policy either partially or simultaneously toward firm value. Ratio of profitability is Return on Equity (ROE) and ratio of dividend policy is Dividend Payout Ratio (DPR). Population of this research are banking firm that list in Indonesia Stock Exchange (IDX). The sample used purposive sampling method and result ten banking firms that used as samples in this research. Data for this research is secondary data. Independent variables for this research are ROE and DPR, and dependent variable is firm value. Method that use are classic assumptions test with multiple regression. Result of this research, the influence between ROE and DPR toward firm value are significant simultaneously. Partially, only ROE can explain significantly toward firm value, while DPR do not influence significantly.Keyword: ROE, DPR and firm value